Deciphering the epidemic synergy of herpes simplex virus type 2 (HSV-2) on human immunodeficiency virus type 1 (HIV-1) infection among women in sub-Saharan Africa. - Ghebremichael, Musie; Habtzgi, Desale; Paintsil, Elijah (BMC research notes, 2012)
Herpes Simplex Virus Type 2 (HSV-2) is highly prevalent in regions disproportionately affected by the human immunodeficiency virus (HIV-1) epidemic. The objective of our study was to identify the risk factors of HSV-2 and HIV-1 infections and to examine the association between the two infections.
Keywords: Adult; Age Factors; Coinfection; Cross-Sectional Studies; Epidemics; Female; Herpes Genitalis; Herpesvirus 2, Human; HIV Infections; HIV-1; Humans; Male; Multivariate Analysis; Prevalence; Risk Factors; Tanzania; Urban Population; Young Adult